Adiposity and hypertension associated risk factors in young (<40 yr) urban industrial men from Pune, India - Mankar, Amol Prakash; Gaigaware, Pooja Bhimshankar; Rao, Shobha Suryaprakash (Indian Journal of Community Health, 2017)
Background: Prevalence of hypertension is not only on the rise in urban population, but its precedence is of concern. Aims & Objective: To identify risk factors associated with hypertension among urban young Indian males. (<40yr). Material & Methods: Young males (<40yr) working in Hinjewadi industrial area of Pune, Maharashtra were studied (n=254) for anthropometry, blood pressure and diet, lifestyle, and stress at work. Results: Prevalence of overweight was 72.5% and 48.4 % were obese while 38.2% were centrally obese (WC?90). Prevalence of hypertension (HTN) was high (25.6%) and showed significant association only with BMI. Non vegetarian diet was a risk factor (OR-1.94;p<0.05) for overweight while lifestyle factors increased risk for obesity (OR-2.1;p<0.05) as also central obesity (OR-1.91;p<0.05). Among subjects with high BMI, these factors became non-significant and stress alone showed independent influence on HTN (OR-4.43; p<0.05) indicating that their influence was mediated through adiposity. Conclusion: Promoting good dietary practices, healthy lifestyle and better work environment for reducing obesity and consequent risk of NCDs among young urban males is essential in India.